(untitled) (Texas Journal of Medical Science, 2023)
Systemic lupus erythematosus (SLE) is a chronic autoimmune multisystem disease predominantly affecting women in the childbearing period. The majority of the pathology in SLE is related to deposits of immune complexes in various organs, which trigger complement and other mediators of inflammation. SLE is characterized by a very large spectrum of clinical manifestations accompanied by prototypic abnormalities of the immune system. Methods: This study was conducted on thirty SLE patients who were diagnosed according to the American College of Rheumatology (ACR) revised criteria. The patient was selected from the outpatient clinic of Rheumatology and Rehabilitation of Ain Shams University Hospital. Fifteen subjects, matched for age and sex, were included in the study and served as a control group. Comparison of quantitative variables between the study groups was done using the Kruskal Wallis analysis of variance (ANOVA) test with Mann Whitney U test for independent samples as posthoc multiple 2-group comparisons. A probability value (p-value) less than 0.05 was considered statistically significant. All statistical calculations were done using computer programs Microsoft Excel 2007 (Microsoft Corporation, NY, USA) and SPSS (Statistical Package for the Social Science; SPSS Inc., Chicago, IL, USA) version 15 for Microsoft Windows. Results and Discussion: Our results come in agreement with the study done by Farzaneh and his colleagues in 2013, who studied fifty-two lupus patients; urinary lipocalin-2 levels in LN patients were significantly higher than those in non-LN patients. Also, our results were in accordance with the study done by Hammad, who studied 33 children with active SLE (22 with and 11 without LN) and compared them with 15 matched controls. Levels of urinary NGAL were higher in patients with LN than those without LN. These findings come in consistent with previous work done by Youssef and his co-worker in 2015, who studied 44 SLE patients and divided them into two groups, group I (twenty-two patients with LN) and group II (twenty-two patients without LN), the urinary lipocalin-2 had the highest mean levels in LN patients (group I) compared to group II and controls with a statistically significant difference. Also, between SLE patients without nephritis (group II) and controls. Conclusions: In this study, urinary lipocalin-2 was significantly higher in the SLE patients compared to the control group, and the lupus nephritis patients, when compared to the patients with SLE without nephritis,showed significantly higher levels of urinary lipocalin-2. The significant association of the urinary lipocalin-2 with the renal SLEDAI shows that urinary lipocalin-2 can be an early biomarker to diagnose patients with lupus nephritis and to detect renal disease activity.